Aislamiento, identificación y pruebas in vitro de cepas autóctonas de Bacillus subtilis como agente de biocontrol de Alternaria spp en Brassica oleracea var.italica. - Ñacato Suntaxi, Carolina Aracely (2016)
There is an increasing consumer demand for quality food, a concept which mainly involves the availability of disease-free products and harmful to human health chemical waste, which is why the need for new options for sustainable management arises broccoli crop against the causative pathogen damage in inflorescence. The disease caused by the phytopathogenic fungus Alternaria spp is a major cause of damage to broccoli cultivars. Field sampling and laboratory investigations were conducted; field soil samples randomly taken broccoli cultivars, plant samples showed signs of being that infected with Alternaria spp collected. In the laboratory stage it proceeded to the isolation, identification and in vitro of Bacillus subtilis strains for the control of Alternaria spp tests; the antagonistic capacity was measured using the scale Bell, the results indicated that the strain ATCC 6633 and strain AB-4 identified and characterized as Bacillus subtilis subsp. licheniformis, they showed antagonistic activity with a value of 21.58% class 2 as measured Bell, thus determined the potential of Bacillus subtilis as biocontrol good against Alternaria spp.